The Relationship between Self-Management Hypertension with Blood Pressure in Elderly: A Cross Sectional Study - Bakar, Shabilla Fasa Noor; Sari, Sheizi Prista; Komariah, Maria (GLOBAL HEALTH SCIENCE GROUP, 2024)
Hypertension is a serious degenerative disease because it affects the condition of the heart, brain, kidneys, and other organs. Hypertension management can be done by implementing hypertension self-management to control blood pressure and reduce morbidity and mortality rates. Lack of self-management in hypertensive patients can affect the severity of the disease and cause complications. This study aims to determine the relationship between hypertension self-management and blood pressure in the elderly in the working area of Jatinangor Community Health Center. This study is a quantitative study with a cross-sectional approach. The study respondents were elderly people with hypertension who were registered in seven Posbindu in the working area of Jatinangor Community Health Center and did not experience complications, totalling 133 respondents. Data were collected during Posbindu activities and home visits using a hypertension self-management questionnaire and blood pressure measurements using a digital sphygmomanometer. The data were analysed with Rasch Model to convert the scale into interval and then Spearman rank correlation test was conducted. This study showed no significant relationship between hypertension self-management and blood pressure in the elderly in the working area of Jatinangor Community Health Center with P-value=0.319 (P>0.05) on systolic blood pressure and P-value=0.285 (P>0.05) on diastolic blood pressure. Despite the absence of a significant relationship, there was a negative correlation between self-management and blood pressure. Thus, improved self-management was associated with decreased or normalized blood pressure among the elderly. This study serves as a valuable reference for future researchers interested in exploring hypertension self-management interventions specifically tailored to the elderly population.